Pengaruh Perencanaan Anggaran dan Pengendalian Intern terhadap Akuntabilitas Publik pada Pemerintah Daerah Provinsi Banten - Juwita, Rakhmini (Jurnal Reviu Akuntansi dan Keuangan)
Accountability is one of the principle of good governance, thus it can be assumed that goodaccountability can improve good governance. The important things to create public accountability, especially in government agencies, are with budget planning and internal control. Budgetplanning includes the general policy formulation of Regional Development Budget (APBD) untilthe arrangement of APBD with the purpose of using government funds can be on the right target,thus that funds are used effectively and efficiently. Budget planning and internal control are themost strategic activity in state finances management because it relates with public accountability. This research aims to know the effect of budget planning and internal control towardpublic accountability in regional government of Banten province. This research used descriptiveexplanatory method by using non probability sampling method at 6 (six) Regional Work Unit(SKPD) in regional government of Banten province. Data analysis which used wasmultiple linear regression. The result of this research shows that budget planning and internal control havethe positive and significant effect toward public accountability in regional government of Bantenprovince. It means that better budget planning and internal control can improve public accountability to be better too.Kata kunci: Perencanaan anggaran, pengendalian intern dan akuntabilitas publik (Abstraktidak dalam bahasa inggris)